2008
DOI: 10.1111/j.1365-2265.2008.03192.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and characteristics of TBII‐seronegative patients in a population with untreated Graves’ hyperthyroidism: a prospective study

Abstract: The prevalence of TBII-seronegativity in untreated patients with GH is 5.4% using a second generation assay. TBII-seronegative patients have biochemically less severe thyrotoxicosis and no Graves' orbitopathy. TBII-seronegative and TBII-seropositive patients apparently belong to the same population of GH, albeit the severity of the autoimmune attack is less in TBII-seronegative patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(35 citation statements)
references
References 35 publications
(60 reference statements)
2
32
0
Order By: Relevance
“…We also observed a decrease in the clinical severity of Graves' hyperthyroidism with age as evident from the fall in the HSS score. There was furthermore a shift toward smaller goiter size in elderly patients, a finding again explainable from the direct relationship between TBII and goiter size (10). Other studies also reported a lower frequency of symptoms and signs in elderly Graves' hyperthyroidism patients (notably less heat tolerance, less perspiration, less irritability, and less often increased appetite, tachycardia and goiter), although weight loss and atrial fibrillation are more common in old age (20)(21)(22).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…We also observed a decrease in the clinical severity of Graves' hyperthyroidism with age as evident from the fall in the HSS score. There was furthermore a shift toward smaller goiter size in elderly patients, a finding again explainable from the direct relationship between TBII and goiter size (10). Other studies also reported a lower frequency of symptoms and signs in elderly Graves' hyperthyroidism patients (notably less heat tolerance, less perspiration, less irritability, and less often increased appetite, tachycardia and goiter), although weight loss and atrial fibrillation are more common in old age (20)(21)(22).…”
Section: Discussionmentioning
confidence: 77%
“…The mechanism behind less severe Graves' hyperthyroidism in the older age groups is incompletely understood. Less severe Graves' hyperthyroidism is due to lower levels of thyrotropin-binding inhibitory immunoglobulin (TBII) (10). Furthermore, it has been shown that advancing age is associated with a decreased experience of selfreported stress (pleasant and unpleasant life events) (11).…”
Section: Introductionmentioning
confidence: 99%
“…Through first-, second-, and third-generation modification, TBII has been modified to enhance its diagnostic sensitivity and specificity for Graves' disease (GD). [6][7][8] Classical TBII assays are limited by their inability to discriminate between thyroid-stimulating antibodies (TSAbs) and thyroid-blocking antibodies (TBAbs). However, the most newly developed thirdgeneration TBII assay inhibits binding of a labeled TSAb (monoclonal Ab clone #M22) rather than labeled TSH to the TSH receptor 9,10 This results in enhanced sensitivity and specificity vs earlier assays using radiolabeled TSH.…”
Section: Introductionmentioning
confidence: 99%
“…It might be that advancing age is associated with greater concern on the significance of symptoms and on health in general, leading to earlier consultation. Longer duration of symptoms until diagnosis was associated with greater goiter size, which can be understood from the longer exposure time to TBII in view of the thyroid growth promoting effect of TBII (13,14). Longer duration of symptoms was also related to higher TPO-Ab concentrations, tentatively explained from epitope spreading after the initial immune reaction against the TSH receptor (15).…”
Section: Discussionmentioning
confidence: 99%